Values and value conflicts in snack providing of Dutch, Polish, Indonesian and Italian mothers. (January 2019) - Damen, Femke W.M.; Hofstede, Gert Jan; Steenbekkers, Bea L.P.A.; Vitaglione, Paola; Pellegrini, Nicoletta; Fogliano, Vincenzo; Luning, Pieternel A.
Abstract: This study investigates which values play a role in the decision of mothers about snacks to offer to their young children with a focus on the value conflicts that might occur. The study explores whether national culture is reflected in mothers' values in snack choice for their young children and the related value conflicts. Semi-structured interviews with 67 mothers of 2–7 years old children divided over 4 national cultures (Dutch, Polish, Indonesian and Italian) were conducted. Questions were asked about their values and value conflicts when providing a snack to their young children. Four key themes could be distinguished to cluster the mentioned values. The health-related key theme includes all values that are associated with the healthiness of the product, the child-related key theme all values that connects to the child, the time-related key theme includes the value convenience and the product-related key theme includes all values that are associated with the product itself. Dutch and Polish mothers mostly valued health of the snack, whereas Indonesian and Italian mothers mostly valued the preference of their child. Data also shows specific prevalence between values and nationalities: convenience was very important for Dutch mothers, valuing organic food was typical for Polish mothers, religion played a role for Indonesian mothers, while Italian mothers placed more value on brand compared to the mothers of other cultures. In all cultures, the value conflicts mentioned were mainly related to health. Highlights: Values in snack providing are health, child, time and product-related. Convenience is highly valued by Dutch mothers. Italian and Indonesian mothers highly value child's preference. Polish mothers value organic and natural snacks. Despite cultural differences, value conflicts were mainly health-related.